2020
DOI: 10.4028/www.scientific.net/msf.1004.376
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Analysis of Individual Partial Dislocations in 4H-SiC Epilayers

Abstract: Configurations of the basal plane dislocations in 4H-SiC epitaxial layers are classified into two types, having typical combinations of ‘straight Si-core and straight C-core’ and ‘straight Si-core and curved C-core’ partial dislocations. The core species are determined by the photoluminescence images and observation of the moving Si-core partial dislocations by ultra-violet light illumination. Each partial dislocation was analyzed by photoluminescence spectroscopy. As the results, C-core partial dislocations h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…The 1SSFs of T1 and T3 had a right-angled corner on the right side, and these two types are the most frequently observed and repo rted. 3,[5][6][7][9][10][11][12][13][14]16,[19][20][21][22] However, the 1SSFs of T2 had a triangular shape with a right-and-left in contrast to T1 and T3. The expansion direction of T2, which was from the surface to the substrate/epilayer interface, was opposite to that of T3.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The 1SSFs of T1 and T3 had a right-angled corner on the right side, and these two types are the most frequently observed and repo rted. 3,[5][6][7][9][10][11][12][13][14]16,[19][20][21][22] However, the 1SSFs of T2 had a triangular shape with a right-and-left in contrast to T1 and T3. The expansion direction of T2, which was from the surface to the substrate/epilayer interface, was opposite to that of T3.…”
Section: Resultsmentioning
confidence: 93%
“…7 In addition, many analyses have been conducted of these 1SSFs, including current/temperature stress testing, [8][9][10][11][12][13][14] calculations, [15][16][17][18] and crystal analysis. [19][20][21][22][23] The BPD detection by photoluminescence (PL) imaging and the use of a buffer layer between the substrate and the epitaxial layer was proposed as a method for controlling 1SSF expansion 4,7,11,24 with the aim of solving the V F degradation issue.…”
Section: Introductionmentioning
confidence: 99%
“…This curved line could not be explained by the elastic stress acting on the PD line but by the formation of a mixture of 30 °C-core and 90 °Ccore PDs. 40) In this epitaxially grown region, it is reasonable to think of the step flow during the epitaxial growth as the most effective driving force to bend the dislocation lines within the basal plane. This might be the reason why one of the immobile PDs changed into a mobile 30°Si-core PD.…”
Section: Discussionmentioning
confidence: 99%
“…28) Although 1SSF expansion and contraction phenomena have been closely examined experimentally [29][30][31][32][33] analytically, [34][35][36] and theoretically, 37,38) the structure of the PDs that constitute the 1SSF remains to be fully elucidated and demonstrated experimentally, particularly in real power devices such as PiN diodes. 39,40) According to the analytical approach, it has been concluded that the combination of 30 °C-core and 90 °C-core PDs in the BPD produce no expansion. 35) Finding the condition that can form these combinations is therefore a significant issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation